Improved Reanalysis and Prediction of Atmospheric Fields Over the Southern Ocean Using Campaign‐Based Radiosonde Observations. Issue 20 (18th October 2018) - Sato, Kazutoshi; Inoue, Jun; Alexander, Simon P.; McFarquhar, Greg; Yamazaki, Akira
Abstract: This study investigated the impact of radiosonde observations from the Southern Ocean obtained by the Australian R/V Aurora Australis on the ALERA2 experimental ensemble reanalysis data set and ensemble forecast experiment. An observing system experiment (OSE) that included additional ship‐launched radiosonde data captured the atmospheric structure over the Southern Ocean. ALERA2 without additional radiosondes had positive temperature biases exceeding 7 °C in the upper troposphere when low‐pressure cyclonic systems passed over the ship. The spread in the upper level was reduced by 15% in the OSE, which propagated downstream from the ship's position because of the sparse observing network over southern high latitudes. Comparison of two 63‐member ensemble forecast experiments initialized by ALERA2 and the OSE revealed that prediction of midlatitude cyclone tracks was improved by the realistic representation of upper‐level troughs in the OSE forecast. This confirms that additional radiosondes over the Southern Ocean reduce uncertainty and error in midlatitude cyclone forecasts. Plain Language Summary: Accurate weather forecasts over the Southern Ocean are required for reducing severe damage for ship operations over the high latitudes and social activities over the midlatitudes in the Southern Hemisphere. However, the sparseness of the observing network over the Southern Ocean causes failures in predicting the low‐pressure systems. This study investigated the impact of additional observations over the Southern Ocean obtained by the Australian R/V Aurora Australis on prediction skill of forecasting systems for weather over the Southern Hemisphere. We revealed that the initial conditions in the reanalysis data, which is used for operational weather forecasts, were improved by the additional radiosonde observations at upper levels, contributing to a more accurate reproduction of a low‐pressure system over the midlatitudes in Southern Hemisphere. This confirms that additional radiosondes launched from ships over the Southern Ocean reduce errors in midlatitude cyclone forecasts. Key Points: Additional observations reduced temperature biases at upper troposphere Observational signals with smaller uncertainties propagated downstream over the Southern Ocean Additional radiosonde observations improved forecast skill of a extratropical cyclone track in the Southern Hemisphere